A Study of Significance and Relationship among Indigenous Knowledge in Science Teaching: Integrating Indigenous Knowledge into Science Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
People's lives can only be improved by science, which is a fundamental discipline that helps people grow as individuals and as a society. A scientific approach has always been used to study the world, and human progress has always relied only on scientific discoveries. Scientific knowledge must be examined critically in light of the current electronic and technological revolution in order to mobilise its constructive application in the most favourable way. Scientific research and indigenous knowledge can both play a role in the formation of human values, especially when they are integrated. Only the traditional and cultural knowledge of an entire society, culture, and civilization constitute indigenous knowledge. It fosters a more optimistic outlook on environmental sustainability, biodiversity preservation, and resource management. There are positive effects on students' values and attitudes if indigenous knowledge and science are integrated. To learn and practise science, one must first have a strong sense of morality, ethics, and values. In this work, indigenous knowledge is explored in terms of how it might be incorporated into science instruction to affect social, cultural, and attitudinal change, particularly among students. The goal is to learn about indigenous conceptions of human existence and how they might be included into secondary school scientific curricula, if not earlier.